Biomarkers of radiation‐induced vascular injury. Issue 2 (3rd December 2018) - Venkatesulu, Bhanu Prasad; Sanders, Keith L.; Hsieh, Cheng‐En; Kim, Byung Kyu; Krishnan, Sunil
Abstract: Objective: Cancer survivorship has thrown the spotlight on the incidence of nonmalignant chronic diseases in cancer patients. Endothelial injury is increasingly recognized as a consequence of cancer treatment, particularly after radiation therapy (RT). This review is to provide a current understanding on the pathophysiological mechanisms and predictive biomarkers of radiation‐induced vascular injury. Recent findings: Radiation directly impacts vasculature by causing endothelial apoptosis and senescence, and alterations in normal homeostasis. This altered milieu at the endothelial surface may contribute to a systemic chronic inflammatory state that is superimposed upon the cascade of normal senescence processes leading to acceleration of age‐related disorders, atherosclerosis, and chronic fibrosis. Vasculature imaging, blood‐based or cell‐component biomarkers, and signatures of genomics, proteomics, metabolomics, and radiomics are potential tools for detection of vascular damage after irradiation. Conclusions: Development of a valid prediction model by combining an array of imaging tools, blood‐based biomarkers, coupled with novel predictors like exosomes and metabolic degradation products can serve to identify RT‐induced vascular injury early for subsequent introduction of newer therapeutic approaches to counter radiation morbidity.